Organizational Commitment as Mediating the Relationship Between Spiritual Leadership on the Sharia Hotels Performance: Organizational Commitment as Mediating the Relationship Between Spiritual Leadership on the Sharia Hotels Performance - Mariyanti, Eka; Husin, Nor Azilah (Advances in Social Sciences Research Journal, 2020)
The purpose of this study is to look at the role of organizational commitment as a mediator between spiritual leadership and Sharia Hotels performance in Padang City, Indonesia, with a sample size of 50 respondents, and this study uses path analysis. The results showed that spiritual leadership has a positive and significant effect on organizational commitment with a significant value of 0.000 < 0.05. Organizational commitment has a positive and significant effect on Sharia Hotels Performance with a significance value of 0.000 < 5%. Spiritual leadership also has a positive and significant effect on Sharia Hotels Performance of 0.000 < 5%. The influence of spiritual leadership on Sharia Hotels’ performance with Organizational Commitment as a mediating variable with a calculated t value of 2.78> t table of 1.6787.